Unemployment among female graduates / Masrul Hayati Kamarulzaman ... [et al.] - Kamarulzaman, Masrul Hayati; Zainal Abidin, Nurain Farahana; Idris, Asma’ Rashidah; Mohd Zaid, Noor Azila; Zoolkefli, Zuliana (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Across the years, the problem of unemployment among female graduates has drawn attention from all across the world. According to statistics on university enrollment, the percentage of females enrolled in tertiary education (certificate, diploma, and degree programmes) increased by almost 20% between 2000 and 2009, and by 2010, there were 60.1% of female studentsenrolled in public tertiary institutions (MWFCD, 2014). Recent data from Statista's Research Department (2022) reveals that more female students than male students were enrolled in higher education in the year 2020. In comparison to 234.08 thousand male students, 358.6 thousand female students were enrolled in public higher education institutions, according to statistics. Since 2016, there has been a decline in the number of male students enrolled in higher education, which is in line with the global trend of more women than males enrolling in such institutions.